Prospective evaluation of an ultrathin strut biodegradable polymer-coated sirolimus-eluting stent: 12 months’ results from the S-FLEX UK registry - Scot Garg; Nikhil Patel; Anirban Choudhury; Jamie Smith; Andrew Sharp; Sergio Nabais de Araujo; Anoop Chauhan; Benjamin Wrigley; Sudipta Chattopadhyay; Azfar G Zaman (BMJ Open)
Objective To prospectively evaluate safety and efficacy of the ultrathin strut biodegradable polymer-coated Supraflex sirolimus-eluting stent (S-SES) in ‘real world’ patient population requiring percutaneous coronary intervention (PCI).Methods National, prospective, multicentre, single-arm, all-comers, observational registry of 469 patients treated with S-SES from July 2015 and November 2016 in 11 centres in UK. Primary endpoint was target lesion failure (TLF) at 12 months (cardiac death, target vessel myocardial infarction (MI) or clinically driven target lesion revascularisation (TLR)). Secondary endpoints included safety and performance outcomes at 12 months—overall stent thrombosis (ST), all-cause mortality, any MI, target vessel failure (TVF) and major adverse cardiac events (MACE—composite of cardiac death, MI, emergent or repeat revascularisation).Results At 12 months, the primary endpoint occurred in 11 (2.4%) of 466 patients, consisting of 4 (0.9%) cardiac deaths, 3 (0.6%) target vessel MI and 7 (1.5%) TLR. Secondary endpoints findings included all-cause mortality in 6 (1.3%), TVF of 14 (3%), no definite ST, 1 (0.2%) probable ST and 3 (0.6%) possible ST. Overall MACE was observed in 18 (3.9%).Conclusions The S-FLEX UK registry showed that the S-SES is safe with a low incidence of TLF in routine clinical practise in patients with coronary artery disease being treated by PCI.